Attack of the stuff : "the life and times of Bill Waddler" - Benton, Jim (Papercutz, 2020)
Bill the duck has an ability--or maybe more of a curse--to hear appliances and objects talk to him, and they really only talk so they can complain and make fun of him--his toilet, who wants to be a movie star, always complains when he makes his morning bathroom run. However, when the Internet disappears and starts making demands, Bill is the only one who can save the world.